A survey of the genes encoding trehalose-metabolism enzymes in crustaceans. Issue 2 (21st April 2023) - Huang, Yuting; Shi, Qiong
Abstract: Trehalose is important in activity, development, and environmental-stress response, especially in invertebrates. It is mainly synthesized by trehalose-6-phosphate synthase (TPS) and trehalose-6-phosphate phosphatase (TPP), and degraded by trehalase (TRE). In the present study, the tps, tpp, and tre were identified from various crustacean species and their phylogeny, structure, network, and transcriptome were analyzed. The tps and tpp are fused in crustaceans, accompanied with multi-copies of genes to improve the synthesis capacity of trehalose, and they may be formed by whole-genome duplication (WGD) and/or segmental duplications. Phylogenetic subgroups of enzymes in the same species may be due to the different lengths and distribution positions of domains. The protein with single TPP domain in the salmon louse, the copepod Lepeophtheirus salmonis (Krøyer, 1837), probably has a depoisoning effect. Structure analyses and location predictions showed that crustacean TRE possess an α-helix-rich structure with barrel core, and are membrane-bound, cytoplasmic, and secreted. Additionally, the non-acid TRE might not be adjusted by Ca 2+ because there is no binding domain in crustaceans. Expression profiles of different tissues, developmental periods, and environmental-challenge responses, as well as genes of co-expression networks suggested that TPS (including TPP) and TRE might play important roles in physiological activities including development and environmental adaptation in crustaceans. Multi-copies of tre may enhance survival ability of copepods in diverse and sometimes harsh environments. Branchiopods, copepods, and the marine shrimp Penaeus vannamei Boone, 1931 are suspected to adopt possible acid TRE as a supplementary strategy in response to stress.